تولية الكافر على المسلم في ولاية الحكم عند ابن تيمية - Ahmad Muqorobin; Ahmad Rayhan (Sultang Agung Islamic University, 2018)
Leader is a very urgent figure in our daily life. In this case a lot of questions about the ideal leader figure who is able to lead this country. The reality is very difficult to find the ideal leader figure, until finally many discourses that say that the leader is not important Muslims or infidels. The most important factor is that he should be able to lead his community fairly. Religious issues are not considered because religion and the state are different things. This led to differences of opinion among 'ulama-'ulama Islam . This research focus to know the opinion of Ibn Taymiyyah related to problems of leadership infidels against Muslims in the government. Research this using type of literature research with normative approach for more in-depth discussion and can achieve the purpose of the background of the problem . In collecting these data the author use the method of documentation to collect the works of Ibn Taimiyah . Furthermore , the author uses the method of deduction to explain the biography of Ibn Taymiyah and the general view of kafir leadership. From sight general the researchers take the essence of the kafir's leadership over a Muslim and a natural government . In order for the analysis to be accomplished more deeply, the author develops his analysis by using descriptive analysis techniques. The result of this discussion concludes that Ibn Taymiyyah forbade kafir leaders to lead a majority Muslim government , and the words of Ibn Taymiyya who said that 'justice is the absolute prerequisite of a leader, and Allah helps a state that is' just though infidels', due to the time of Ibn Taymiyah there are so many Muslim leaders who do not apply 'justly, so this can only apply in that time and circumstance. The kafir leader can not lead justly because a kafir has not been able to deal justly with himself by not believing in Allah SWT.